Introduction to computer graphics and multimedia - Mukhopadhyay,Anirban (Vikas, 2011)
Introduction to computer graphics and multimedia / Mukhopadhyay,Anirban. -- Kolkata: Vikas, 2011 006.6 M954e2 2nd ed. No. of Copies : 1